PEMULIHAN TERPIDANA PENGGUNA NARKOBA DI PUSAT YAYASAN REHABILITASI NARKOBA AR-RAHMAN PALEMBANG - Mgs Nazarudin; Jumanah Jumanah (Universitas Islam Negeri Ar-Raniry, 2019)
Drug abuse problems have broad and complex dimensions, both from the medical, psychiatric, mental health and psychosocial perspectives. The use of drugs can damage the order of family life, the environment of the community and the school environment, even directly or indirectly a threat to the sustainability of development and the future of the nation and the State. The results in this study are in rehabilitating the Ar-Rahman foundation using emphasis on four main aspects, namely the recovery of physical, mental, spiritual and emotional. The recovery program for 6 months, in the reception of residents or addicts, does not limit the related services such as the BNN, but the family and the community play an important role, the majority of residents at the ArRahman foundation enter with coercion from their parents or family and. From the results of research conducted related to social rehabilitation of drug abuse carried out by the ArRahman Drug Rehabilitation Foundation, it has helped in returning or repairing addicts from drug dependence so that they can re-function as social beings. This is in accordance with the objectives of Islamic law or MaqashidShari'ah to maintain reason. Therefore rehabilitation can be done.